Interaction nets: programming language design and implementation - Hassan, Abubakar; Mackie, Ian; Sato, Shinya (Electronic Communications of the EASST, 2008)
This paper presents a compiler for interaction nets, which, just like term rewriting systems, are user-definable rewrite systems which offer the ability to specify and program. In the same way that the lambda-calculus is the foundation for functional programming, or horn clauses are the foundation for logic programming, we give in this paper an overview of a substantial software system that is currently under development to support interaction based computation, and in particular the compilation of interaction nets.